2017
DOI: 10.1186/s12936-017-1777-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance mediating Plasmodium falciparum polymorphisms and clinical presentations of parasitaemic children in Uganda

Abstract: Background Plasmodium falciparum genetic polymorphisms that mediate altered drug sensitivity may impact upon virulence. In a cross-sectional study, Ugandan children with infections mutant at pfcrt K76T, pfmdr1 N86Y, or pfmdr1 D1246Y had about one-fourth the odds of symptomatic malaria compared to those with infections with wild type (WT) sequences. However, results may have been confounded by greater likelihood in those with symptomatic disease of higher density mixed infections and/or recent prior treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition, the findings of the current study also revealed that the pfmdr1 86 Y mutation and the YF SND haplotype occurred more at low parasitaemia, which is consistent with findings by earlier studies elsewhere 57 59 . Although causality cannot be inferred, the association between the pfmdr1 86 Y mutation and the parasitaemia level has been linked to multiplicity of infection and parasite virulence, with parasites with decreased virulence carrying the mutant pfmdr1 86 Y allele 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the findings of the current study also revealed that the pfmdr1 86 Y mutation and the YF SND haplotype occurred more at low parasitaemia, which is consistent with findings by earlier studies elsewhere 57 59 . Although causality cannot be inferred, the association between the pfmdr1 86 Y mutation and the parasitaemia level has been linked to multiplicity of infection and parasite virulence, with parasites with decreased virulence carrying the mutant pfmdr1 86 Y allele 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In a region of very high malaria transmission intensity, children harbouring P. falciparum containing mutations associated with resistance to CQ and AQ were less likely to be febrile suggest that wild-type parasites are more capable of causing clinical illness than those with resistance-mediating mutations in pfcrt and pfmdr1 [40]. Our results indicated that, the prevalence of pfcrt was similar among the residence areas, except for pfmdr1whose prevalence was the lowest in Sacred Heart primary school.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the ndings of the current study also revealed that the pfmdr1 86Y mutation and the YFSND haplotype occurred more at low parasitaemia, which is consistent with ndings by earlier studies elsewhere 48,49,50 . Although causality cannot be inferred, the association between the pfmdr1 86Y mutation and the parasitaemia level has been linked to multiplicity of infection and parasite virulence, with parasites with decreased virulence carrying the mutant pfmdr1 86Y allele 50,51 .…”
Section: Discussionmentioning
confidence: 99%